Differences in reporting food insecurity and factors associated with differences among Latino fathers and mothers - Sayaka Nagao-Sato; Stephanie Druziako; Aysegul Baltaci; Alejandro Omar Peralta Reyes; Youjie Zhang; Ghaffar Ali Hurtado Choque; Marla Reicks (BMC Public Health, 2021)
Abstract Background Food security status has been assessed as a representative score for households; however, different members in the same household may perceive and report food insecurity differently. A high prevalence of food insecurity has been reported among Latino households, therefore understanding differences in reporting food insecurity by Latino father-mother dyads may improve accuracy of assessment and plans to address food insecurity. This study aimed to 1) determine demographic characteristics and/or food-related factors associated with perceptions of food security status among Latino father-mother dyads, and 2) identify factors associated with discordance in perceptions of food insecurity between dyads. Methods Baseline data were used from a community-based, youth obesity prevention program among Latino families (n = 106 father-mother dyads). Food security was assessed with a 2-item food insecurity screen. Logistic regression models were used to evaluate associations between reporting food security status and predictor variables for fathers, mothers, and dyad-discordant responses. Results Food insecurity was reported by 39% of fathers and 55% of mothers. Adjusted odds of reporting food insecurity were significantly higher for fathers perceiving their neighborhood was unsafe vs. safe (OR: 3.7, p < 0.05) and reporting lower vs. higher household income (OR: 3.2, p < 0.05). Adjusted odds of reporting food insecurity were significantly higher for mothers perceiving their neighborhood was unsafe vs. safe (OR: 4.1, p < 0.01) and reporting lower vs. higher home availability of fruit and vegetable (OR: 5.5, p < 0.01). Dyad discordance in reporting food security status occurred in 24% of the dyads. Adjusted odds of dyad discordant reports of food insecurity status were significantly higher for dyads reporting discordant responses regarding previous nutrition education (OR: 3.4, p < 0.05) and higher home fruit and vegetable accessibility (OR: 3.1, p < 0.05) compared to dyads reporting concordant responses. Among the 28 dyads who reported discordant nutrition education participation, 21 reported that fathers had never participated but mothers had participated more than once. Conclusions Differential factors were associated with reporting food security among Latino father-mother dyads. Nutrition education for fathers that improves awareness of home food supplies and a better understanding of how food accessibility influences maternal perceptions may improve dyad discordance in reporting household food security.